Can vein patch interposition after sapheno-femoral ligation prevent postoperative neovascularization at the saphenofemoral junction? - Goda, Asser Abd El-Hamid (International Surgery Journal, 2018)
Background: Majority of recurrence of varicose veins following both primary and repeated surgery was attributable to neovascularization. The aim of this study was to evaluate the efficacy and safety of the new natural origin anatomical barrier (vein patch) in decreasing neovascularization after initial surgery. Methods: The study included 50 patients with primary varicose vein and incompetence of SFJ. The patients are divided randomly into 2 groups, group (A) (conventional surgical group) and group (B) (barrier technique group), each one included 25 patients. In group (A) SFJ ligation with ligation of all the tributaries and stripping of great saphenous vein (GSV) in the thigh portion was done. In group (B), after conventional surgical procedure was done vein patch was taken from striped LSV. The vein patch was applied on the cribriform fascia opening. This barrier of vein patch is reinforced by good tight subcutaneous tissue suture. Results: Neovascularization was seen on duplex in 4 (16%) limbs of group (A) conventional surgical group at one year follow up, but in group (B) barrier technique group neovascularization was seen only in one (4%) limb. Groin infection was registered in 3 (12%) limbs, 2 (8%) of them in group (A) conventional surgical group and the third one (4%) in the group (B) barrier technique group. Conclusions: Vein patch interposition after correctly SFJ ligation seems to lower the incidence of neovascularisation after one year. This technique may constitute additional option to prevent recurrence.